PERLINDUNGAN KONSUMEN MAKANAN KEMASAN KADALUWARSA ASIA TOSERBA GARUT (PUTUSAN MA NO. 504K/PDT.SUS/BPSK/2021 ) - Paskah Aprilia Silalahi; Siti Nurbaiti (Fakultas Hukum Universitas Trisakti, 2021)
Food products always include the expiration date number, but consumers pay less attention to the expiration date, which can be detrimental to consumers. One example is the case that occurred at the Asia Department Store in Garut. Formulation of the problem: how to provide compensation to consumers at the Asia Department Store in Garut and whether the Supreme Court Decision No. 504K/Pdt.Sus/BPSK/2021 is in accordance with the Consumer Protection Law. The research method used is descriptive normative legal research using secondary data and primary data which is used to support secondary data, the analysis is carried out qualitatively with deductive conclusions drawn. Research results, discussion and conclusions describe that the compensation given to consumers by the Asia Department Store in Garut is not in accordance with what was proposed by the consumer and the Supreme Court Decision No. 504K/Pdt.Sus/BPSK/2021 is not in accordance with the Consumer Protection Law.